Acceptance of Modern Retail Consumers Towards Internet of Things (IOT) Technology with Tam Approach Method - Agus Bonatua Situmorang; Lizar Alfansi (Universitas Negeri Semarang, 2024)
This research aims to investigate consumer acceptance of Internet of Things (IoT) technology in the context of modern retail by applying the Technology Acceptance Model (TAM). TAM is used to analyze consumer perceptions of the usefulness and ease of use of IoT technology, particularly in information systems, smart checkout, and smart displays in the retail environment. The population used in this research consists of modern retail consumers who use IoT devices, with a sample of 300 respondent individuals. Data were collected through a Google Form questionnaire and then subjected to validity and reliability tests to evaluate the fit and reliability of the proposed model. The study also analyzed the relationship between exogenous and endogenous variables and conducted hypothesis testing using PLS-SEM. The research results indicate that all proposed hypotheses have a positive and significant impact. These findings provide in-depth insights into consumer responses and acceptance of IoT technology in modern retail. The implications of these findings can assist stakeholders, including retailers and technology developers, in designing more effective marketing strategies and enhancing the acceptance of IoT technology in the modern retail environment. Thus, this research highlights the significant potential of IoT in transforming the modern retail industry.